Use of computational fluid dynamics to compare upper airway pressures and airflow resistance in brachycephalic, mesocephalic, and dolichocephalic dogs. (November 2019) - Fernández-Parra, R.; Pey, P.; Zilberstein, L.; Malvè, M.
Highlights: A computer-assisted methodology for evaluating airflow resistance in different dog breeds was proposed. Three dog types (dolichocephalic, mesocephalic and brachycephalic; n  = 3/group) were studied. Reconstructions in 3D were performed from computerized images and computational fluid dynamic analysis was performed in each dog. Pressure and airway resistance was computed for each dog; brachycephalic dogs had higher values than other breeds. These results may increase clinical understanding of the brachycephalic syndrome. Abstract: Brachycephalic dog breeds are prone to breathing difficulties because of their upper airway anatomy. Several surgical techniques exist to correct anatomical pathologies and common surgical approaches aim to correct functional abnormalities in the nares and/or the soft palate. However, further research is needed to improve clinical outcomes. This study evaluated air pressure and airflow resistance in the upper airways and trachea in nine sedated, sternally recumbent dogs of different skull types (dolichocephalic, n  = 3; mesocephalic, n  = 3; brachycephalic, n  = 3). CT images were acquired from the nostrils to the caudal border of the lungs and geometrical reconstruction of the upper airway and trachea was performed. Analysis of computational fluid dynamics was performed using inspiratory flow adapted to bodyweight for each dog. Flow (L/min) and pressure (cmH2 O) were computed for the entire upper airway and trachea. Resistance (cmH2 O/L/min) was calculated using pressure differences between the nose, larynx, and trachea. In this pilot study, statistical comparisons were not performed. Pressure maps, airflow, and resistance were similar in dolichocephalic and mesocephalic breeds. Median pressure difference (3.76 cmH2 O) and resistance (0.154 cmH2 O/L/min) between the nose and larynx were numerically higher in brachycephalic dogs than in other breeds (0.45 cmH2 O and 0.016 cmH2 O/L/min, respectively). Median pressure difference (0.205 cmH2 O) and resistance (0.009 cmH2 O/L/min) between the larynx and trachea was numerically similar in all dogs, except for the English bulldog. The methodology used in this preliminary study to quantify airflow characteristics such as pressure and resistance could improve the understanding of brachycephalic obstruction airway syndrome.